The Possible effect of Adult Functional Literacy Education on Farmer Production in Kersa Woreda; South Western Ethiopia (Global Journal of Human-Social Science, 2017)
This paper deals with the impacts of functional adult literacy education on farmer's production. Identifying the means through which functional adult literacy increases and/or decreases farmers' production, and finding out associated advantages and negative side of the program are the objectives of the study. In depth interview was used to collect primary data from purposively selected respondents. Besides the secondary data were also collected from secondary sources to strengthen the findings of the paper. There by qualitatively analyzed results show that being provided functional adult literacy in the study area through cooperation of health, education and agricultural sectors, one to five productive army farmers, and mobilization by benefits and increment of participants has a lot of advantages such as economic growth, human, social, and physical capitals development, and social services development. However, lack of contextualizing the program, lack of some community's members willingness, lack of standard materials, and low emphasize from other sectors are considered as the problems associated the role of functional adult literacy in boosting farmers' production. Thus, making this program as an integrative issue for all ministries and developing policy accordingly may results in stated goals of our country to reach at middle income countries by boosting the participation of small holder farmers in agricultural and rural development.